2020
DOI: 10.1111/jocn.15402
|View full text |Cite
|
Sign up to set email alerts
|

Family members' lived experiences when a loved one undergoes an interhospital intensive care unit‐to‐unit transfer: A phenomenological hermeneutical study

Abstract: Aims and objectives To reveal meanings of family members' lived experiences when a loved one undergoes an interhospital intensive care unit‐to‐unit transfer. Background Interhospital intensive care unit‐to‐unit transfers take place between different hospitals and their respective intensive care units (ICUs). These types of transfers are an increasing phenomenon but are sparsely studied from the family members' perspective. Indeed, the patient's critical illness and care can have a major impact on family member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 37 publications
4
12
1
Order By: Relevance
“…Through consideration of the participants’ experiences of a family member’s IFT for advanced critical care services, both challenging and beneficial aspects of experience were identified. As with previous studies, family members in the present study experienced concerns about managing responsibilities at home while away at the urban center, fear and uncertainty related to traveling to an unfamiliar city and hospital, worry that something would happen to their relative while enroute to the urban center, and, for some, concern related to how they would manage financially ( Johnson, 1999 ; Karlsson et al, 2020 ; Mackie et al, 2014 ). These findings also overlap with transfer experiences for other health-related indications, such as pregnancy-related conditions ( Woodhart et al, 2018 ) or cancer-related care ( Chua et al., 2022 ).…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Through consideration of the participants’ experiences of a family member’s IFT for advanced critical care services, both challenging and beneficial aspects of experience were identified. As with previous studies, family members in the present study experienced concerns about managing responsibilities at home while away at the urban center, fear and uncertainty related to traveling to an unfamiliar city and hospital, worry that something would happen to their relative while enroute to the urban center, and, for some, concern related to how they would manage financially ( Johnson, 1999 ; Karlsson et al, 2020 ; Mackie et al, 2014 ). These findings also overlap with transfer experiences for other health-related indications, such as pregnancy-related conditions ( Woodhart et al, 2018 ) or cancer-related care ( Chua et al., 2022 ).…”
Section: Discussionsupporting
confidence: 59%
“… Karlsson et al (2020) and Mackie et al (2014) indicated that receiving information from health care providers that is honest and complete is beneficial for family members and the absence of this is distressing, which was an experience echoed by participants in the present study. However, despite this need for information, participants in the present study often described an aversion or reticence to communicating with health care providers or even being present in the critical care area for fear of “bothering” health care providers.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations